Development of SatuJantung 2.0 Revised Version Android Application for Cardiac Arrest Pre-Hospital Management - Beta Ahlam Gizela (Journal of Community Empowerment for Health, 2023)
Cardiac arrest is one of the leading causes of death in Indonesia. Deaths can be prevented if symptoms are recognized early, and immediate assistance can be provided. An Android application called SatuJantung 2.0 was developed in 2018 and has been in use. However, during evaluation in implementation, it was found that the application is not compatible with the latest version of Android. An application revision is needed with newer features.The objective of this study is to develop a revised version of SatuJantung 2.0 with more advanced specifications. Methods used is action research, consist of 4 cycles: 1) Planning, 2) Action, 3) Observation, 4) Reflection.Final result of this study is an android application named SatuJantung 2.0 revised version. This application is developed in Bahasa Indonesia. This application has menu for login, registration, user profile, user status (based on analysis of user profile by risk calculator), user information, summary, emergency button, guidance for the first responders, sending WhatsApp message for the family/contact registered with the geotag location, and emergency call to ambulance.SatuJantung 2.0 revised version, named SatuJantung 2.5, provides an easy way for patients calculate the risk factors, get information about the disease and management, ask help in emergency situation, and guide first responders to do prehospital management in cardiac arrest case.